Evolution of in vivo assessed retention forces in one‐piece mini dental implant‐retained mandibular overdentures: 5‐Year follow‐up of a prospective clinical trial. (16th July 2019) - Abou‐Ayash, Samir; Enkling, Norbert; Srinivasan, Murali; Haueter, Marius; Worni, Andreas; Schimmel, Martin
Abstract: Background: The evolution of retention forces in one‐piece mini dental implants (MDIs) retaining implant overdentures (IODs) is of major importance, as the male parts cannot be exchanged, due to the implant design. Purpose: To report the evolution of retention forces of one‐piece MDIs, retaining mandibular IODs with ball/ O‐ring attachments during 5 years assessed in vivo. Materials and Methods: Four MDIs were installed in the interforaminal region and immediately loaded using the existing mandibular complete denture. Directly post‐op, at the 1‐year and the 5‐year follow‐up, the retention forces were assessed with a validated strain gauge at each implant site separately. Results: At the male part, changes could only be observed at implant site 34: During the first year, there was a statistically significant increase, whereas the retention forces were decreased at the 5‐year follow‐up. At the female part, retention forces decreased significantly over time. Baseline values could be reestablished by exchanging the O‐rings. The changes of the retention forces were more obvious in the posterior, compared to the anterior implants. Conclusions: Retention forces at the female part decrease significantly over time, when retaining mandibular IODs by MDIs with ball/ O‐ring attachments. Baseline values can be reestablished by exchanging the O‐rings. At the male part, changes of retention forces depend on the implant location.